2013
DOI: 10.1124/dmd.113.053330
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Inhibition Kinetics of (S)-Warfarin Hydroxylation by Noscapine: Implications in Warfarin Therapy

Abstract: Noscapine is an antitussive and potential anticancer drug. Clinically significant interactions between warfarin and noscapine have been previously reported. In this study, to provide a basis for warfarin dosage adjustment, the inhibition kinetics of noscapine against warfarin metabolism was characterized. Our enzyme kinetics data obtained from human liver microsomes and recombinant CYP2C9 proteins indicate that noscapine is a competitive inhibitor of the (S)-warfarin 7-hydroxylation reaction by CYP2C9. Interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…A similar isotope effect encountered in the in vivo insecticide synergizing activity of these compounds firmly confirms the mechanistic association between the formation of CO and the MI complex, with consequent P450 inhibition [165] Three mechanistic pathways are plausible for oxidation of the MDP-dioxymethylene bridge to the iron-coordinated carbene: In the first, hydroxylation of the dioxymethylene bridge followed by elimination of a water molecule results in an acidic oxonium ion that upon deprotonation gives the carbene (Fig 53, path a)In the second, formation of the oxonium species could precede generation of the bridge-hydroxylated metabolite, if the ferryl species were to oxidize the radical formed in the hydroxylation reaction before the oxygen rebound occurs (Fig 53, path b (Fig 54), a selective serotonin reuptake inhibitor (SSRI) [166][167][168][169][170][171][172][173] In vitro studies with purified CYP2D6 indeed reveal the formation of MI complex es with the characteristic spectroscopic signature at 456 nm [172] The intermediacy of a carbene is further supported by the fact that paroxetine is metabolized by CYP2D6 via demethylenation of the MDP group to a catechol and formic acid [169,173] The K I and k inact values of 6.6 ± 2.7 μM and 0.25 ± 0.09 min − 1 , respectively, calculated for the paroxetine-mediated inhibition of human liver microsomal CYP2D6-dependent dextromethorphan O-demethylation [172], are fully consistent with clinical reports of its potent CYP2D6 inhibition [166][167][168][169][170][171][172][173] Another noteworthy example of an MDP-bearing drug is noscap- (Fig 54), a nonaddictive, phthalideisoquinoline alkaloid derived from the opium poppy latex, and widely recognized as a safe and promising cough suppressant as well as a potential cancer chemotherapeutic agent when administered at much higher doses [174][175][176][177] At antitussive doses, significant clinical DDIs of noscapine were repor...…”
Section: Catalysis-dependent Inhibitionsupporting
confidence: 64%
“…A similar isotope effect encountered in the in vivo insecticide synergizing activity of these compounds firmly confirms the mechanistic association between the formation of CO and the MI complex, with consequent P450 inhibition [165] Three mechanistic pathways are plausible for oxidation of the MDP-dioxymethylene bridge to the iron-coordinated carbene: In the first, hydroxylation of the dioxymethylene bridge followed by elimination of a water molecule results in an acidic oxonium ion that upon deprotonation gives the carbene (Fig 53, path a)In the second, formation of the oxonium species could precede generation of the bridge-hydroxylated metabolite, if the ferryl species were to oxidize the radical formed in the hydroxylation reaction before the oxygen rebound occurs (Fig 53, path b (Fig 54), a selective serotonin reuptake inhibitor (SSRI) [166][167][168][169][170][171][172][173] In vitro studies with purified CYP2D6 indeed reveal the formation of MI complex es with the characteristic spectroscopic signature at 456 nm [172] The intermediacy of a carbene is further supported by the fact that paroxetine is metabolized by CYP2D6 via demethylenation of the MDP group to a catechol and formic acid [169,173] The K I and k inact values of 6.6 ± 2.7 μM and 0.25 ± 0.09 min − 1 , respectively, calculated for the paroxetine-mediated inhibition of human liver microsomal CYP2D6-dependent dextromethorphan O-demethylation [172], are fully consistent with clinical reports of its potent CYP2D6 inhibition [166][167][168][169][170][171][172][173] Another noteworthy example of an MDP-bearing drug is noscap- (Fig 54), a nonaddictive, phthalideisoquinoline alkaloid derived from the opium poppy latex, and widely recognized as a safe and promising cough suppressant as well as a potential cancer chemotherapeutic agent when administered at much higher doses [174][175][176][177] At antitussive doses, significant clinical DDIs of noscapine were repor...…”
Section: Catalysis-dependent Inhibitionsupporting
confidence: 64%
“…The biological functions of a-NF have been shown to be involvedi ni nhibiting aromatase, drug transporters and platelet aggregation, as wella si nducing apoptosis, thus contributing to the treatmento fc ancer anda rterial thromboembolism. [79][80][81][82] Additionally,arecent study revealed that a-NF has aclearstimulatory effect on the ovaries, and prevents both systemic and gonadal 3-methylcholanthrene-induced toxicity. [83] In particular, a-NF has attracted considerable interest in modulating cyto-chromeP 450s.…”
Section: Interactions Of Naphthoflavonoids With Cyp1smentioning
confidence: 99%
“…The time‐dependent inhibition of CYP3A4 and CYP2C9 by noscapine could explain the clinical noscapine–warfarin interaction . Because of noscapine's inhibitory effects, (S)‐warfarin exposure is predicted to increase up to sevenfold when administered alongside noscapine . These pharmacokinetic interactions between warfarin and noscapine indicate that careful monitoring of the international normalized ratio for blood coagulation will be required when noscapine is combined with warfarin.…”
Section: Caution! Noscapine Teams Up With Warfarinmentioning
confidence: 99%